Discovering the potential of an nZVI-biochar composite as a material for the nanobioremediation of chlorinated solvents in groundwater: Degradation efficiency and effect on resident microorganisms. (October 2021) - Semerád, Jaroslav; Ševců, Alena; Nguyen, Nhung H.A.; Hrabák, Pavel; Špánek, Roman; Bobčíková, Kateřina; Pospíšková, Kristýna; Filip, Jan; Medřík, Ivo; Kašlík, Josef; Šafařík, Ivo; Filipová, Alena; et al.
Abstract: Abiotic and biotic remediation of chlorinated ethenes (CEs) in groundwater from a real contaminated site was studied using biochar-based composites containing nanoscale zero-valent iron (nZVI/BC) and natural resident microbes/specific CE degraders supported by a whey addition. The material represented by the biochar matrix decorated by isolated iron nanoparticles or their aggregates, along with the added whey, was capable of a stepwise dechlorination of CEs. The tested materials (nZVI/BC and BC) were able to decrease the original TCE concentration by 99% in 30 days. Nevertheless, regarding the transformation products, it was clear that biotic as well as abiotic transformation mechanisms were involved in the transformation process when nonchlorinated volatiles (i.e., methane, ethane, ethene, and acetylene) were detected after the application of nZVI/BC and nZVI/BC with whey. The whey addition caused a massive increase in bacterial biomass in the groundwater samples (monitored by 16S rRNA sequencing and qPCR) that corresponded with the transformation of trichloro- and dichloro-CEs, and this process was accompanied by the formation of less chlorinated products. Moreover, the biostimulation step also eliminated the adverse effect caused by nZVI/BC (decrease in microbial biomass after nZVI/BC addition). The nZVI/BC material or its aging products, and probably together with vinyl chloride-respiring bacteria, were able to continue the further reductive dechlorination of dichlorinated CEs into nonhalogenated volatiles. Overall, the results of the present study demonstrate the potential, feasibility, and environmental safety of this nanobioremediation approach. Graphical abstract: Image 1 Highlights: Novel nano iron-biochar composite (nZVI/BC) was tested to remediate contaminated groundwater. NZVI/BC followed by biostimulation transformed chlorinated ethenes (CEs). CEs were dechlorinated into less toxic nonhalogenated volatiles. 16S rRNA sequencing revealed development of an organohalide-respiring community. Living bacterial biofilm was detected on nZVI/BC using fluorescence microscopy.